Implementation of Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) Method in Determining The Best Employees - Yuyun Dwi Lestari; Arief Budiman; Dedy Irwan; Anggi Hanafiah (The IJICS (International Journal of Informatics and Computer Science), 2022)
Employees are one of the wealth owned by the company. Employees are also able to advance the company and benefit the company if the employee has good performance. Therefore, decision makers in the company must determine the best employees in order to motivate their employees to work well. Decision makers are often faced with difficulties in decision making with so much data. To avoid this, a decision support system can be used with the method of MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS (MOORA) which can help determine the best employees by using predetermined criteria and weights. The criteria used are attendance, letter of reprimand, appreciation, responsibility and timely reporting of duties. This Moora method can help users in determining the Best Employees with optimization values based on these criteria.